Counseling Group and Games Education in Developing English Language for Students’ Elementary School - Suhono Suhono (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
The Article analyzed Counseling Group and Games Education in Developing English Language for Students in elementary school. The researcher used the steps for a literature review to obtain scientific evidence (Snyder, 2019; Peters et al., 2020), that is, of counseling groups and games education in developing the English language for students in elementary school. Hence, the researchers have visited several scientific publications on several applications, for instance, Eric Publications, Google Book, Taylor, and France, and many others. In comparison, the review process involves several stages. First, giving coded the data, evaluated and looked for relevance, and interpreted it in depth to conclude if the findings were relevant in answering valid questions. Based on the review, many kinds of publications showed that Innovative games could be in the form of educational games. Educational games are created using computer technology by taking into account the peculiarities, language development, and theories of acquiring children's language so that children are not easily bored in recognizing or learning English vocabulary. Therefore, English educational games can be used to develop English vocabulary.